Hyperinflammation and Fibrosis in Severe COVID-19 Patients: Galectin-3, a Target Molecule to Consider - Garcia-Revilla, Juan; Deierborg, Tomas; Venero, Jose Luis; Boza-Serrano, Antonio (Frontiers in Immunology, 2020)
COVID19 disease have become so far the most important sanitary crisis in the XXI century. In light of the events, any clinical resource should be considered to alleviate this crisis. Severe COVID-19 cases present a so-called cytokine storm as the most life-threatening symptom accompanied by lung fibrosis. Galectin-3 has been widely described as regulator of both processes. Hereby, we present compelling evidences on the potential role of galectin-3 in COVID-19 in the regulation of the inflammatory response, fibrosis and infection progression. Moreover, we provide a strong rationale of the utility of measuring plasma galectin-3 as a prognosis biomarker for COVID-19 patients and propose that inhibition of galectin-3 represents a feasible and promising new therapeutical approach.